"We and us, not I and me": Justice, social capital, and household vulnerability in a Nova Scotia fishery. (May 2015) - Barnett, Allain J.; Eakin, Hallie C.
Abstract: Marine harvesters face significant livelihood challenges due to the impacts of climate change on marine ecosystems, and due to economic fluctuations that influence their incomes. In this study, we demonstrate vulnerability as a product of the interactions among marine harvesters, government and buyers. We combined Elinor Ostrom's attention to the influence of institutions on resource exploitation, with political ecology's attention to perceptions of agency, and the contribution of justice and equity to measuring the success of institutions. We demonstrate the benefits of this approach by examining the multi-species fishery of Barrington, Nova Scotia. We conducted 31 semi-structured interviews and 113 surveys in the summer of 2012 with buyers, harvesters, and local experts. We used Ostrom's SES framework to pinpoint system elements that were salient to respondents, with attention to household vulnerability outcomes. Based on an analysis of these themes, we outline three processes affecting vulnerability outcomes: 1) Harvesters preferred individual over collective action due to low procedural justice and social cohesion in decision-making, 2) agents with greater political and economic power gained control over fishing access-rights while others became more dependent on lobster, and 3) economic and ecological conditions, combined with increased dependence, incentivized harvesters to catch more lobsters as prices declined. The case suggests that actors sense of control over their resource base and perception of justice in the process of institutional design may be as significant in vulnerability as the exogenous drivers of change that affect livelihood outcomes. We suggest interventions that may improve these interactions among government, harvesters and buyers, and improve the livelihoods in coastal communities. Highlights: We examined interactions through which actors influence and respond to institutions. Fishing communities in SWNS had weak social ties to each other and to government. Some actors gained greater control over the access to fishing quota and licenses. Lobster-dependent harvesters were most vulnerable to economic and ecological change. An actor's sense of control over resources and procedures influences vulnerability.